2013
DOI: 10.5194/acp-13-12233-2013
|View full text |Cite
|
Sign up to set email alerts
|

Biogenic and biomass burning organic aerosol in a boreal forest at Hyytiälä, Finland, during HUMPPA-COPEC 2010

Abstract: Abstract. Submicron aerosol particles were collected during July and August 2010 in Hyytiälä, Finland, to determine the composition and sources of aerosol at that boreal forest site. Submicron particles were collected on Teflon filters and analyzed by Fourier transform infrared (FTIR) spectroscopy for organic functional groups (OFGs). Positive matrix factorization (PMF) was applied to aerosol mass spectrometry (AMS) measurements and FTIR spectra to identify summertime sources of submicron aerosol mass at the s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
89
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 72 publications
(105 citation statements)
references
References 116 publications
(178 reference statements)
15
89
1
Order By: Relevance
“…GAINS underestimated the Aitken mode particle concentrations more heavily than AeroCom, by a factor of two to three in Hyytiälä, Värriö and Kpuszta, suggesting that the higher condensation sink associated with higher accumulation mode particle emissions in GAINS had a significant impact on modeled ultra-fine particle number concentrations. In addition, Hyytiälä and Värriö are regions in which BVOC emissions and clean air are the key influencing factors for new particle formation and particle growth (Ruuskanen et al, 2007;Corrigan et al, 2013;Liao et al, 2014). This was reflected in the model results: particle number size distributions in Hyytiälä and Värriö were quite similar between the two simulations based on different anthropogenic emission data sets.…”
Section: Simulated Particle Number Concentrations and Size Distributionssupporting
confidence: 64%
“…GAINS underestimated the Aitken mode particle concentrations more heavily than AeroCom, by a factor of two to three in Hyytiälä, Värriö and Kpuszta, suggesting that the higher condensation sink associated with higher accumulation mode particle emissions in GAINS had a significant impact on modeled ultra-fine particle number concentrations. In addition, Hyytiälä and Värriö are regions in which BVOC emissions and clean air are the key influencing factors for new particle formation and particle growth (Ruuskanen et al, 2007;Corrigan et al, 2013;Liao et al, 2014). This was reflected in the model results: particle number size distributions in Hyytiälä and Värriö were quite similar between the two simulations based on different anthropogenic emission data sets.…”
Section: Simulated Particle Number Concentrations and Size Distributionssupporting
confidence: 64%
“…The correlation of total organic acids to OA and m/z 44 was also observed at Hyytiälä, during the spring 2013 (Figures 1e-1h) and HUMPPA-COPEC 2010 studies (Figures 1i-1l) [Corrigan et al, 2013;Vogel et al, 2013]. In this boreal forest, 45-51% of OA mass is accounted for by organic molecules containing at least one acid group.…”
Section: 1002/2015gl064650mentioning
confidence: 72%
“…This is higher than that observed during BEACHON-RoMBAS. Corrigan et al [2013] note that the high OA mass concentration during HUMPPA-COPEC 2010 is due to aged biomass burning plumes advected from forest fires in central Russia, together with unusually high temperatures in Finland during the campaign period leading to enhanced biogenic SOA formation. Thus, the enhanced aging and/or biomass burning impacts may explain the higher organic acid concentration observed during the HUMPPA-COPEC 2010.…”
Section: 1002/2015gl064650mentioning
confidence: 99%
See 1 more Smart Citation
“…A particularly prominent example is the fire-driven air pollution episode of summer 2010 in western Russia, which affected not only Russia itself but also other parts of Northern Europe [60] and even southern Europe [58], as mentioned earlier. For a boreal forest in Hyytiälä, Finland, using two independent analytical methods and three separate statistical methods, Corrigan et al [61] showed that biomass burning is responsible for 25 % of submicron organic aerosols in the area, especially in the relatively warm and dry months of summer.…”
Section: Aerosolsmentioning
confidence: 99%